Is It Possible to Rank Universities Using Fewer Indicators? A Case Study on Five International University Rankings Popular Among Sri Lankan State Universities. - Janen, T.; Kusala Sajeewani, H.W. (Bharathidasan University, 2025)
This study examines the applicability of international university ranking systems to Sri Lankan state universities, focusing on the five most popular systems: Times Higher Education (THE), QS World University Rankings, SCImago Institutions Rankings, University Ranking by Academic Performance (URAP), and Webometrics. These rankings, often used as benchmarks for institutional quality, heavily emphasize research, internationalization, and visibility—areas where Sri Lankan universities face challenges due to resource limitations, reliance on localized indicators, and contextual constraints. The study analyzes the indicators and methodologies of these systems and evaluates their alignment with the strengths and challenges of Sri Lankan universities. Findings reveal that while Sri Lankan universities excel in teaching quality, societal impact, and regional development, they struggle to meet criteria such as international collaborations, citation impact, and industry partnerships that are heavily weighted in global rankings. The study highlights the limitations of using these rankings to fully capture the performance of universities in developing contexts and advocates for a more nuanced evaluation framework that integrates local priorities. Recommendations include phased strategies to improve research output, international visibility, and institutional capacity while aligning with global standards. The findings underscore the need for Sri Lankan universities to balance global competitiveness with their national mission to contribute to societal and economic development.
Keywords: University Ranking Systems; Ranking Indicators; Sri Lankan universities